Spot light on intestinal microbiota - Papineni, Rao V. L.; Umar, Shahid (Translational Cancer Research; Vol 2, No 4 (August 26, 2013): Translational Cancer Research (Nanotechnology in Radiation Research), 2013)
Microbes in human body play an essential role in immunity, health, and disease. The gut microbes have been found to be the most diverse and constitute the densest cell number in the human microbiota and studies continue to support the premise that commensal bacteria, largely anaerobic, serve to maintain microbial stability and colonization resistance by preventing overgrowth or domination with more pathogenic bacteria, through interactions within the microbial community and with the host. Early results have indicated that the imbalances in gut microbiota are related to numerous disorders, such as inflammatory bowel disease, colorectal cancer (CRC), diabetes, and atopy. In patients with immune suppression due to high-dose chemotherapy or hematopoietic stem cell transplantation or in patients undergoing radiation therapy, disruption of the microbiota through antibiotics as well as impairment of host immunity gives rise to perturbations favoring intestinal domination by pathogenic species, leading to increased bacterial translocation and susceptibility to systemic infection. Randomized and double blind placebo-controlled human studies using pro- pre- or synbiotics, with adequate follow-up are needed to formulate directions for prevention and therapy. Nano-formulation of phytonutrients for delivery to specific targets could revolutionize personalized medicine.